Efficacy of Topical 1% Adapalene Versus Cryotherapy in Treatment of Plantar Warts - Arifullah Maj, Muhammad Adeel Siddique, Lt. Col. Majid Hussain (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Warts are spiny, rough papules or nodules that can be found anywhere on skin. They are caused by human papilloma virus (HPV) infection. There are over 100 HPV types documented. Approximately 6% of children and 2% of adults consult the doctor for wart. The aim of the current study was To compare the efficacy of topical Adapalene gel 0.1% under occlusion with cryotherapy in the treatment of plantar wart Methodology: It was Randomized control trial carried out at the Department of Dermatology, Combined Military Hospital, Abbottabad, Pakistan, from Feb 2022 to July 2022. A total of 60 Patients coming to hospital with complaints of plantar warts were randomized into two equal groups of 30 patients. Patients reporting on odd serial number were allocated to group A, treated with application of topical 1% adapalene gel overnight on daily basis under occlusion, while patients reporting on even serial number were allocated to group B, treated with cryotherapy for two freeze thaw cycles, done with liquid nitrogen at -196°C temperature using direct application by a dipstick. The primary outcome was to measure the complete resolution of warts after 8 weeks from start of treatment. Results: Age range in this study was from 18 to 45 years with mean age of 32.366±8.61 years, while duration of disease was from 2 to 12 weeks with mean duration of 6.433±2.90 weeks. After 8 weeks of treatment, 27 patients (90%) in group-A, while 20 patients (66.66%) in group-B achieved complete resolution of warts (p-value 0.028). Practical implication: In the practical implications of this study, while comparing topical adapalene versus cryotherapy in trials, an important fact is that cryotherapy is done under supervision by the physician on fortnightly basis while adapalene is applied under occlusion by patients themselves daily at home, so, a major advantage of use of adapalene gel is also its simplicity and convenience of use. Another advantage to the patient is in shape of painless application at home compared to the cryotherapy. However, one disadvantage with adapalene gel is that it has to be used under occlusion by plastic sheet on daily basis which may feel messy to some patients Conclusion: Topical 0.1 % adapalene was more effective than cryotherapy in the treatment of plantar warts. Keyword: Human papillomavirus, Plantar warts, Adapalene, Cryotherapy.